The impact of workplace stressors on exhaustion and work engagement in policing. (March 2022) - Lockey, Steven; Graham, Les; Zheng, Yuyan; Hesketh, Ian; Plater, Marisa; Gracey, Sara
This paper uses the challenge-hindrance stressor framework to examine the impact of challenge and hindrance stressors on police officer and staff well-being. Results of two studies conducted in English police forces demonstrate that challenge stressors relate positively to the effort and enthusiasm individuals invest into their work. Findings also indicate that while challenge stressors are positively associated with exhaustion cross-sectionally (Study 1, N = 469), they do not impact exhaustion over time (Study 2, N = 823). Conversely, hindrance stressors cause exhaustion in the long-term and are negatively associated with work engagement cross-sectionally. Implications for theory and practice are discussed.